Perizinan Berusaha berbasis Risiko Pemanfaatan Perairan Pesisir Paska UU Cipta Kerja - Nainggolan, Indra Lorenly (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
The Applicability of Law No. 11 of 2020 of Cipta Kerja, signifies the implementation of the concept of risk-based business licensing that shares risks at low, medium, and high levels. This concept is not much different from general licensing which also pays attention to risk as the basis for issuing permits, only that it focuses more on simplifying permits in obtaining them and monitoring them. Indigenous peoples and local communities will compete with other business perpetrator based on the level of risk in accessing coastal waters. The state is responsible for protecting indigenous peoples and local communities, so as not to lose their rights to coastal waters. This paper to study whether risk-based business licensing protects these communities. Meanwhile, the research method used is normative juridical using literature studies.